2023
DOI: 10.3892/ol.2023.13754
|View full text |Cite
|
Sign up to set email alerts
|

Risk of endometrial cancer in patients with polycystic ovarian syndrome: A meta‑analysis

Abstract: While existing literature suggests an association between polycystic ovarian syndrome (PCOS) and endometrial cancer, the sparsity and inconsistency of current evidence indicates a lack of clarity regarding the exact strength of this association. It also remains uncertain whether the degree of risk of disease is affected by confounding factors, such as age and body mass index (BMI). The present meta-analysis is aimed to quantify the risk of endometrial cancer in female subjects with PCOS compared to those witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The hallmarks of PCOS include hyperandrogenism, oligo/anovulation and polycystic ovarian morphology. It is also associated with cardio-metabolic diseases such as obesity and diabetes ( 3 ), psychological disorders ( 4 ) and increased cancer risk ( 5 , 6 ). The disease is multifactorial, and its complex pathophysiology involves multiple pathways ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The hallmarks of PCOS include hyperandrogenism, oligo/anovulation and polycystic ovarian morphology. It is also associated with cardio-metabolic diseases such as obesity and diabetes ( 3 ), psychological disorders ( 4 ) and increased cancer risk ( 5 , 6 ). The disease is multifactorial, and its complex pathophysiology involves multiple pathways ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 32 The prevalence of endometrial cancer has been reported to be increased 3-5 fold in those with PCOS in the postmenopause years, and an increased risk for ovarian cancer has been reported in younger women with PCOS in the premenopause years. 6 , 123 , 124 , 125 In our cohort, we have shown that all malignancy was increased by 30% in those with PCOS, suggesting that increased awareness and screening may be warranted.…”
Section: Discussionmentioning
confidence: 70%
“…This is consistent with the results of a number of meta-analyses of which we are aware. For example a meta-analysis that included 10 studies showed that women with PCOS had a significantly increased risk of endometrial cancer compared to controls (69), with a further increase in risk when postmenopausal people were excluded from the meta-analysis. Similarly, adenomyosis is a benign gynaecological disease, whereas EC can originate from malignant transformation of ectopic endometrium within the adenomyosis lesion, leading to endometrial carcinoma arising in adenomyosis (EC-AIA).…”
Section: A B Cmentioning
confidence: 99%